Modeling for computer graphics study in terms of fundamentalization of information science - Sultangaliyeva L.4, Suleimenova G.5Baidrakhmanova G.A.1, Issabayeva D.N.2, Rakhimzhanova L.B.3, (Opción, 2019)
The research objective consists of consideration and application of a technique for teaching computer graphics by means of information model creation via the method of computer graphics study by means of information models. The results of the pedagogical experiment prove the reliability and effectiveness of the technique connected with computer information modeling in the process of computer graphics teaching. In conclusion, the fundamentalization of education, the course of information science particularly must be constructed from a phenomenon of information processes to methods of their study by means of information models, using computer as a tool to control the information processes.